2012
DOI: 10.1128/mcb.00070-12
|View full text |Cite
|
Sign up to set email alerts
|

GATA6 Is Required for Proliferation, Migration, Secretory Cell Maturation, and Gene Expression in the Mature Mouse Colon

Abstract: e Controlled renewal of the epithelium with precise cell distribution and gene expression patterns is essential for colonic function. GATA6 is expressed in the colonic epithelium, but its function in the colon is currently unknown. To define GATA6 function in the colon, we conditionally deleted Gata6 throughout the epithelium of small and large intestines of adult mice. In the colon, Gata6 deletion resulted in shorter, wider crypts, a decrease in proliferation, and a delayed crypt-to-surface epithelial migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…GATA-4, -5 and -6 are found mainly in the heart and endoderm-derived tissues, including the liver, lungs, pancreas, stomach and intestines 18 . Furthermore, it has been reported that GATA6 is expressed in proliferating cells in the intestinal crypts and is required for crypt cell proliferation and migration 19,20 . Targeted inactivation of the GATA6 gene in mice causes early embryonic lethality due to the lack of endoderm differentiation [21][22][23] .…”
mentioning
confidence: 99%
“…GATA-4, -5 and -6 are found mainly in the heart and endoderm-derived tissues, including the liver, lungs, pancreas, stomach and intestines 18 . Furthermore, it has been reported that GATA6 is expressed in proliferating cells in the intestinal crypts and is required for crypt cell proliferation and migration 19,20 . Targeted inactivation of the GATA6 gene in mice causes early embryonic lethality due to the lack of endoderm differentiation [21][22][23] .…”
mentioning
confidence: 99%
“…1, C and D), although Gata6 loss was incomplete due to inefficient recombination at the Gata6 Fl allele (Fig. 1, D and E) (17). Thus, we refer to these mice as Gata4 del Cdx2 del and note that HNF4A expression was preserved (Fig.…”
Section: Cis-element Features Identify Candidate Partner Tfs In Intes-mentioning
confidence: 89%
“…Indeed, knock-out mice lacking single factors show diverse, subtle, and nonlethal defects. GATA4 and GATA6 show regional (proximal 4/5) and global intestinal expression, respectively, and the corresponding mutant mice have subtle defects in crypt cell replication, secretory cell differentiation, and control of selected enterocyte genes (15)(16)(17). Loss of HNF4A perturbs colon development (18), but Hnf4a ÏȘ/ÏȘ adult mouse intestines are overtly normal, with modestly perturbed gene expression (19).…”
Section: Hnf4a;cdx2 Compound-mutant Intestines Indicated That This Tfmentioning
confidence: 99%
“…Conditional deletion of Gata6 and Gata4 produced a decrease in cellular proliferation in crypts of the small intestine [49] as well as a reduction in proliferating cell numbers in the pancreatic epithelium [50,51]. In addition, Gata4 is thought to regulate cardiomyocyte proliferation through direct activation of the Cyclin D2 and Cdk4 promoters [52], although this does not appear to be a general mechanism (Tevosian et al, unpublished results).…”
Section: Discussionmentioning
confidence: 99%